Introduction to and Screening Visit Results of the Multicenter Pediatric Crohn's Disease Growth Study. Issue 12 (19th March 2020) - Gupta, Neera; Lustig, Robert H; Andrews, Howard; Sylvester, Francisco; Keljo, David; Goyal, Alka; Gokhale, Ranjana; Patel, Ashish S; Guthery, Stephen; Leu, Cheng-Shiun
Abstract: Background: Statural growth impairment is more common in males with Crohn's disease (CD). We assessed sex differences in height Z score differences and bone age (BA) Z scores and characterized age of menarche in a novel contemporary cohort of pediatric CD patients undergoing screening for enrollment in the multicenter longitudinal Growth Study. Methods: Crohn's disease patients (females with chronological age [CA] 5 years and older and younger than 14 years; males with CA 6 years and older and younger than 16 years) participated in a screening visit for the Growth Study. Height BA-Z scores are height Z scores calculated based on BA. Height CA-Z scores are height Z scores calculated based on CA. The height Z score difference equals height CA-Z score minus height BA-Z score. Results: One hundred seventy-one patients (60% male) qualified for this analysis. Mean CA was 12.2 years. Mean height CA-Z score was −0.4, and mean height BA-Z score was 0.4 in females. Mean height CA-Z score was −0.1, and mean height BA-Z score was 0.2 in males. The absolute value of the mean height Z score difference was significantly greater in females (0.8) than males (0.3; P  = 0.005). The mean BA-Z score in females (−1.0) was significantly lower than in males (−0.2; P  = 0.002). The median CA at menarche was 13.6 (95% CI, 12.6–14.6) years. Conclusions: Our screening visit data suggest that standardized height gain is lower in males with skeletal maturation and delayed puberty is common in females in CD. We are investigating these findings in the ongoing Growth Study.